Antibacterial activity of ergosterol peroxide against Mycobacterium tuberculosis - Duarte, Noelia (2015)
Ergosterol peroxide, cycloart-23-en-3 beta,25-diol, vanillin and 4-hydroxybenzaldehyde have been isolated and characterized from a crude methanol extract of Euphorbia lagascae. Previous studies have shown contradictory results about the antibacterial activity of ergosterol peroxide against Mycobacterium tuberculosis. In order to clarify this question, the activity of this compound was tested against Mycobacterium tuberculosis H37Rv ATCC 27294 strain using two different systems: BACTEC 460TB (Bactec 460) and BACTEC MGIT 960 system (Bactec 960). The results obtained show that significant activity was demonstrable only with the Bactec 460 system. The lack of activity noted with the Bactec 960 system appears to be due to the much faster growth rate of the organism in the medium of this system as opposed to that of the Bactec 460 system. Ergosterol peroxide is also shown by the current study to be devoid of any activity against an antibiotic sensitive ATCC strain of Staphylococcus aureus.